Validitas Pengembangan Media Pembelajaran Bagan dan Audio pada Materi Wudhu - Muhammad Rizqi; Ahamad Faujianor (CV. Creative Tugu Pena, 2024)
This study aims to prepare and assess the validity of learning media using charts and audio on ablution material in class VII MTs Muslimat NU Palangka Raya. Given the importance of a deep understanding of ablution in the context of religious education, this study applied the Research and Development (R&D) method with a 4D model limited to development. The needs analysis showed that students experienced a dilemma in understanding the material through conventional methods. Therefore, a media chart depicting the steps of ablution visually, accompanied by audio explaining the pillars and procedures of ablution, was designed to improve students' understanding. The validation results from media and material experts showed that this media was very feasible to use, with an average score of 89.5%. The advantages of this media are its attractiveness and interactivity, although there are some factors that need to be improved, such as adding examples and improving content. This research is expected to provide support for improving fiqh learning methods and become a reference for other educators in creating effective learning media. Further development can be done by adding interactive elements and testing the effectiveness of the media in a wider contex